The effect of green human resource management on environmental performance: Systematic literature review (Lighthouse Publishing, 2023)
Rapid industrialization has caused environmental degradation in recent years. Industrial activities produce global warming, climate change, drought, forest fires, ecological degradation, and environmental damage. Many companies think their business has no environmental impact, yet it does. The organization finally resolved to limit environmental pollution and save resources after seeing the phenomenon. Modern organizations no longer prioritize profitability and business benefits. Companies today prioritize ecologically friendly practices. This Systematic Literature Review collects some of the literature that discusses the influence of GHRM on EP. The research objective is to explore the literature related to the effect of GHRM on EP. This research was compiled using Preferred Reporting Items for Systematic Review and Meta-Analysis. The data collection method uses data inclusion. Some of the literature obtained was 75 literature taken from three sources, namely The Directory of Open Access Journals (DOAJ), Google Scholar, and Scopus with the help of Publish or Perish software. Then a screening was carried out and as many as 30 pieces of literature were obtained. The results show that of the 30 pieces of literature, 27 kinds of literature provide GHRM results with a positive and significant effect on EP. 1 literature shows that GHRM has no significant effect on EP, 1 literature makes GHRM a moderating variable and 1 literature makes GHRM a mediating variable.